Financial ratios and stock return : a panel data analysis - Liaw, Huan Huan (Universiti Malaysia Sarawak (UNIMAS), 2012)
The main objective of this study is to examine the role of the financial ratios such as dividend yield (DIY), book-to-market (B/M) ratio, price earnings (PIE) ratio, size, payout ratio and leverage to predict the stock return for the 5 different sectors in Malaysia from 2006 to 20 I O. Using panel data analysis, the result shows that the financial ratios such as size were the most powerful in predicting the stock return in all sectors. Dividend yields also show the high predictability in stock return in all sectors except banking sector. Besides that, the book-to-market ratios showed the negative significant relati(')nship between stock return in servicing, banking, food producer and construction sectors. However, the financial ratios such as leverage, payout and price earnings ratio were indicated less predictive power to predict the stock return. Therefore, the results imply that investors can rely on the financial ratios such as dividend yields and size information to gain abnormal returns in the market. The results further ind icate that the Malaysian stock market is not informational efficient.